2008
DOI: 10.1152/ajplung.00010.2008
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of acute lung injury

Abstract: Acute lung injury in humans is characterized histopathologically by neutrophilic alveolitis, injury of the alveolar epithelium and endothelium, hyaline membrane formation, and microvascular thrombi. Different animal models of experimental lung injury have been used to investigate mechanisms of lung injury. Most are based on reproducing in animals known risk factors for ARDS, such as sepsis, lipid embolism secondary to bone fracture, acid aspiration, ischemia-reperfusion of pulmonary or distal vascular beds, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
1,397
1
27

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,443 publications
(1,493 citation statements)
references
References 241 publications
33
1,397
1
27
Order By: Relevance
“…Most of the studies using animal models examined the role of macrophages in LPS-induced lung injury, a model that resembles septic ARDS (11,18,20). In this study, we used the model of acid-induced lung injury, a model of aseptic ARDS (2). Similarly to septic lung injury, we found that alveolar macrophages in acid-induced lung injury acquire a classical (M1) activation phenotype in the early phase that is characterized by increased iNOS expression and accumulation of NO metabolites, which are known to contribute to the pathogenesis of ARDS (4,13,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies using animal models examined the role of macrophages in LPS-induced lung injury, a model that resembles septic ARDS (11,18,20). In this study, we used the model of acid-induced lung injury, a model of aseptic ARDS (2). Similarly to septic lung injury, we found that alveolar macrophages in acid-induced lung injury acquire a classical (M1) activation phenotype in the early phase that is characterized by increased iNOS expression and accumulation of NO metabolites, which are known to contribute to the pathogenesis of ARDS (4,13,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Acute lung injury, the pathologic presentation of ARDS, is characterized by alveolar barrier disruption and lung inflammation (2)(3)(4)(5)(6)(7). Two phases of inflammatory response have been recognized in experimental acute lung injury: the acute phase, characterized by inflammatory cell infiltration and increased production of a variety of oxidants, cytokines, and proteolytic enzymes that promote tissue destruction (1,2) and the resolving phase, during which phagocytosis of debris and alveolar structural repair are taking place (1,8,9).…”
mentioning
confidence: 99%
“…The rabbit a rodent to be larger and easier handling was considered appropriate for this research [9][10][11][12][13][14][15][16][17][18][19][20][21] . To these factors is associated with ease of anesthesia protocol, which provided adequate hypnosis and analgesia, an anesthetic for up to 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of genetic manipulation has been carried out in mice, although clearly limitations in translatability of murine models to human disease have been extensively described in recent reviews, with some aspects reviewed briefly below (19,51,65,102). The ability to routinely perform genetic modification in larger mammals will expand our capabilities of carrying out clinically relevant research.…”
Section: Global Transgenic Mice (Or Gene Overexpression In All Tissues)mentioning
confidence: 99%
“…Because it is impossible to do justice to the extensive important findings in lung biology that have been identified through use of modeling genetically modified mice, we have reviewed some of the key findings that have contributed to our basic understanding of COPD, asthma, pneumonia, ARDS, IPF, and pulmonary hypertension (Supplemental Table S1). Although the list is certainly not exhaustive, it is apparent that: 1) critical discoveries have arisen as a result of use of these animal models; 2) the same genetically modified animal has yielded key information regarding disease pathogenesis for multiple illnesses and has contributed substantially to our understanding of human disease; and 3) despite the immense information of these animal models, there exist important limitations in direct translatability of the findings for each lung disease and have recently been reviewed in depth (11,19,65,102,109,144). It is important to understand the limitations of the models themselves, since these factors are of enhanced importance in interpreting findings from genetically modified mice subjected to these models.…”
Section: Discoveries and Pitfalls Of Genetically Modified Mice In Lunmentioning
confidence: 99%